ISOLATION AND PURIFICATION OF ANTICANCER PROTEIN EXOTXIN A FROM Pseudomonas aeruginosa - Jawad, L. Q.; Rasheed, H. A. R. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Toxins produced from bacteria constitute promising antitumor agents in treating different cancer types. Exotoxin A from Pseudomonas aeruginosa is the highly toxic virulence component that bind to specific cell receptors. This study aimed to purify Exotoxin A from clinically isolated Pseudomonas aeruginosa. A total of 150 bacterial isolates were taken from clinical samples (burn and wounds) and were screened on selective media and identified as P. aeruginosa using biochemical analysis and molecular test by PCR amplification technique utilizing specific primer 16srRNA. Exotoxin A produced from P. aeruginosa were screened and purified by two steps that include gel filtration and ion-exchange chromatography. In this study, 68 isolates were characterized as P. aeruginosa, furthermore, real-time PCR proved that these isolates revealed 100% specificity, sensitivity and had positive amplified bands with a size of 249bp. The concentration of Exotoxin A extracted from P. aeruginosa using Trypticase soy broth was 18 Mg/ml. The percent of Purification and recovery for Exotoxin A was 21.4 %, 40% respectively. Clinical Isolates of Pseudomonas aeruginosa have the potential to produce Exotoxin A that is responsible for pathogenicity.